Yours in Filial Regard : The Civil War Letters of a Texas Family - Love (Family : 1828 : Limestone County, Tex (Book collections on Project MUSE., 2015)
"The Love Family Letters archive displays a vast communication network consisting of writers on both home and war fronts spanning the entirety of the Civil War. The inclusion of domestic writers in conjunction with soldiers from varying units of the C.S.A. provides a vital link between two perspectives of the war and an inside look into the Loves' struggle to maintain family ties ... Seventy-seven of the letters are written by the soldiering Love brothers; Cyrus, Sam, James, and John Love, and brother-in-law John Karner; to their parents and sisters in Texas. In addition, the collection preserves three letters circulated between women on the home front, with authors including Fannie Love and Tennessee Love ... The volume presented here is only a representative sample of a much larger body of epistles; absent, sadly, are letters which were received and not preserved, those which are fragmented or excerpted, and the untold number of letters which were miscarried, captured, or otherwise lost in the confusion of war."--Introduction